2016
DOI: 10.1111/jzo.12321
|View full text |Cite
|
Sign up to set email alerts
|

Behavioural responses of pine weevils to non‐consumptive interactions with red wood ants

Abstract: Non-consumptive effects are increasingly recognized as important in predator-herbivore interactions, with both fundamental and practical implications. Notably, feeding damage to conifer seedlings by pine weevils, Hylobius abietis (L.), which are serious pests in forest regeneration areas, can be decreased by interactions with ants (Formicidae). To probe the behavioural mechanisms underlying such effects, which have rarely been described in predator-herbivore systems, we investigated how the ants influence the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…In a recent study, it was also shown that ants attacked pine weevils more frequently and for longer periods around ant‐attended seedlings and the locomotion behaviour of pine weevils increased when attacked by red wood ants, suggesting that weevils are more likely to move away from ant‐attended seedlings (Maňák et al. ). The results of the current study support this hypothesis by showing that the presence of ants reduces the number of pine weevils on the seedlings without any weevils being killed, for example by non‐consumptive interactions.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In a recent study, it was also shown that ants attacked pine weevils more frequently and for longer periods around ant‐attended seedlings and the locomotion behaviour of pine weevils increased when attacked by red wood ants, suggesting that weevils are more likely to move away from ant‐attended seedlings (Maňák et al. ). The results of the current study support this hypothesis by showing that the presence of ants reduces the number of pine weevils on the seedlings without any weevils being killed, for example by non‐consumptive interactions.…”
Section: Discussionmentioning
confidence: 97%
“…In a related study, we found that the locomotion behaviour of pine weevils increased during ant attacks, suggesting that behaviourally mediated effects play an important role in ant–plant protection against pine weevils (Maňák et al. ).…”
Section: Introductionmentioning
confidence: 92%
“…The red wood ants, Formica (Formica) sensu lato are abundant in European forests, and their stable and high population levels make the ants a very important component of the forest ecosystem (Gößwald 1989(Gößwald -1990, Domisch et al 2005, 2009, Sorvari & Hakkarainen 2005, Ohashi et al 2007, Finér et al 2013. In boreal forests, ants are thought to regulate other invertebrates, including pest species, and protect other groups of insects such as aphids against parasites and predators (Moya-Laraño & Wise 2007, Johansson & Gibb 2012, Maňák et al 2016.…”
Section: Introductionmentioning
confidence: 99%